2021
DOI: 10.1186/s12966-021-01164-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the complex food environment underlying dietary intake in low-income groups: a systems map of associations extracted from a systematic umbrella literature review

Abstract: Background Inequalities in obesity pertain in part to differences in dietary intake in different socioeconomic groups. Examining the economic, social, physical and political food environment of low-income groups as a complex adaptive system – i.e. a system of multiple, interconnected factors exerting non-linear influence on an outcome, can enhance the development and assessment of effective policies and interventions by honouring the complexity of lived reality. We aimed to develop and apply no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 76 publications
(164 reference statements)
1
74
0
Order By: Relevance
“…The research also highlights that dietary habits and tastes are both deeply personal and profoundly entwined by emotions and social norms. This finding is consistent with other studies which found that social and cultural factors, food beliefs and perceptions influenced dietary behavior among refugees and vulnerable groups [ 28 , 29 , 30 ]. This means that people do not make decisions around food choices and nutrition in isolation or based solely on health outcomes or perceived health benefits.…”
Section: Discussionsupporting
confidence: 93%
“…The research also highlights that dietary habits and tastes are both deeply personal and profoundly entwined by emotions and social norms. This finding is consistent with other studies which found that social and cultural factors, food beliefs and perceptions influenced dietary behavior among refugees and vulnerable groups [ 28 , 29 , 30 ]. This means that people do not make decisions around food choices and nutrition in isolation or based solely on health outcomes or perceived health benefits.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, future studies should examine overweight and obesity using systems dynamics approaches. Such approaches model overweight and obesity as part of a complex system [62][63][64], and could thereby move beyond bivariate exposure-outcome associations.…”
Section: Discussionmentioning
confidence: 99%
“…Household deprivation also plays a significant role in the nutrition behaviours of children (29,31) . Evidence suggests that household food insecurity may lead to the selection of relatively cheap and unhealthy foods, and may also decrease an individual's motivation to eat healthily (11) . In New Zealand, 20% of children aged 0-15 years live in households that report that food 'ran out often' or 'sometimes', making it difficult to consume nutritionally balanced diets (30) .…”
Section: Economic Environmentmentioning
confidence: 99%
“…Intervention approaches that exclusively target individual-level determinants such as knowledge, beliefs and habits have little or no impact long term (9,10) . However, in combination with environmental-change components these individual approaches have greater effectiveness in improving health behaviours (10,11) .…”
mentioning
confidence: 99%